2018
DOI: 10.1007/s00018-018-2773-4
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of the plasma extracellular vesicle proteome after separation from lipoproteins

Abstract: The isolation of extracellular vesicles (EVs) from blood is of great importance to understand the biological role of circulating EVs and to develop EVs as biomarkers of disease. Due to the concurrent presence of lipoprotein particles, however, blood is one of the most difficult body fluids to isolate EVs from. The aim of this study was to develop a robust method to isolate and characterise EVs from blood with minimal contamination by plasma proteins and lipoprotein particles. Plasma and serum were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
523
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(563 citation statements)
references
References 40 publications
35
523
5
Order By: Relevance
“…Lipo‐NPs are envisioned for future autologous applications, but could also have potential allogeneic uses considering that BiNPs are frequently exchanged between individuals in the clinical setting. For example, plasma transfusions seldom cause adverse reactions,79 although this biological fluid contains a large amount of BiNPs from various cells 80. Moreover, it is possible that Lipo‐NPs could be lyophilized to aid in storage for clinical applications.…”
Section: Resultsmentioning
confidence: 99%
“…Lipo‐NPs are envisioned for future autologous applications, but could also have potential allogeneic uses considering that BiNPs are frequently exchanged between individuals in the clinical setting. For example, plasma transfusions seldom cause adverse reactions,79 although this biological fluid contains a large amount of BiNPs from various cells 80. Moreover, it is possible that Lipo‐NPs could be lyophilized to aid in storage for clinical applications.…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate whether a specific MDA‐MB‐231 EV signal could be detected in each of the spiked samples, we identified seven putative MDA‐MB‐231 EV proteins which are not reported in the healthy plasma EV proteome dataset by Karimi et al . but are reported in the MDA‐MB‐231 EV proteome published by Hurwitz et al .…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate whether a specific MDA-MB-231 EV signal could be detected in each of the spiked samples, we identified seven putative MDA-MB-231 EV proteins which are not reported in the healthy plasma EV proteome dataset by Karimi et al [17] but are reported in the MDA-MB-231 EV proteome published by Hurwitz et al [28] and functionally implicated in MDA-MB-231 cell activity. [29][30][31][32][33][34][35] The LC-MS/MS data (total intensity, % coverage, # unique peptides) for 6-phosphogluconate dehydrogenase (PGD), ADP-ribosylation factor 1 (ARF1), eukaryotic elongation factor 2 (EEF2), Rab GDP dissociation inhibitor beta (GDI2), heterogeneous nuclear ribonuclear protein K (HNRNPK), syntenin-1 (SDCBP) and vimentin (VIM) are summarized in Table 1.…”
Section: Functional Enrichment Analysis Was Performed For Biologicalmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteomic profiles of MSC‐EV isolated by SEC are likely to differ from those of MSC‐EV isolated by ultracentrifugation, HPLC, tangential flow filtration, or precipitation, as SEC is likely to better remove overabundant soluble proteins compared to other techniques, resulting in relatively more pure EV preparations. Thus, comparative studies on SEC‐isolated MSC‐EV, with a strong focus on EV purity and potential contaminations will be required to verify our conclusions on MSC‐EV cargo and their potential functional implications …”
Section: Discussionmentioning
confidence: 99%